Gotyk w służbie oficjalnej narracji o Ziemiach Zachodnich? Przewodnik po zabytkach Wrocławia z informatorem w kontekście architektonicznych uwarunkowań Wrocławia w latach 40. XX w. - Rosner-Leszczyński, Kacper; Bekieszczuk, Krzysztof (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
This article presents the role of architecture in the process of making the landscape of the Western and Northern Territories of Poland in the late 1940s more familiar to new inhabitants. The topic is analyzed on the example of Wroclaw city guidebook from 1948 by St[anislaw] Sevatt. In his work, special focus was given to gothic churches in order to emphasize close relations between Silesia and the other regions of Poland in the time of the Piast dynasty.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne